Exploring the adsorption ability with sensitivity and reactivity of C12–B6N6, C12–Al6N6, and B6N6–Al6N6 heteronanocages towards the cisplatin drug: a DFT, AIM, and COSMO analysis. Issue 45 (18th October 2022) - Muktadir, Md. Golam; Alam, Ariful; Piya, Afiya Akter; Shamim, Siraj Ud Daula
Abstract : Studied the most sensitive and reactive nanocages towards the cisplatin anticancer drug. Abstract : The DFT study on the adsorption behaviour of the C24, B12 N12, and Al12 N12 nanocages and their heteronanocages towards the anticancer drug cisplatin (CP) was performed in gas and water media. Among the three pristine nanocages, Al12 N12 exhibited high adsorption energy ranging from −1.98 to −1.63 eV in the gas phase and −1.47 to −1.39 eV in water media. However, their heterostructures C12 –Al6 N6 and B6 N6 –Al6 N6 showed higher interaction energies (−2.22 eV and −2.14 eV for C12 –Al6 N6 and B6 N6 –Al6 N6 ) with a significant amount of charge transfer. Noteworthy variations in electronic properties were confirmed by FMO analysis and DOS spectra analysis after the adsorption of the cisplatin drug on B12 N12 and B6 N6 –Al6 N6 nanocages. Furthermore, an analysis of quantum molecular descriptors unveiled salient decrement in global hardness and increments in electrophilicity index and global softness occurred after the adsorption of CP on B12 N12 and B6 N6 –Al6 N6 . On the other hand, the above-mentioned fluctuations are not so noteworthy in the case of the adsorption of CP on Al12 N12, C12 –B6 N6, and C12 –Al6 N6 . Concededly, energy calculation, FMO analysis, ESP map, DOS spectra, quantum molecular descriptors, dipole moment, COSMO surface analysis, QTAIM analysis, and work function analysis predict that B12 N12 and B6 N6 –Al6 N6 nanocages exhibit high sensitivity towards CP drug molecules.